Activities of the Lithuanian Mathematical Society in 2004–2007 - Kubilius, Jonas (Lietuvos matematikos rinkinys, 2007)
The article gives a survey of activities of the Mathematical Society during last three years. Some poblems of he mathematical life in Lithuania are rised.
Keywords: Lithuanian Mathematical Society